Web-based Inventory Tracing Design in Hospitality - Dadan Suhamdani; Ryo Benhard Dahlian (International Journal of Information System and Innovative Technology, 2022)
Hotel is a type of accommodation or a provider of facilities and services for lodging, food, beverages and Convention Hall. Where in a hotel will have a lot of inventory and stock of goods needed for the operation of the hotel. Information systems are very important and much needed in hospitality. One of these information systems is the inventory system. With the inventory system, the hotel can manage, control and track all required inventory and stock of goods. The inventory system can simplify the analysis of stock requirements that must be met by the hotel, control the location of stock storage and find out the stock that has been used. A case study in designing inventory tracing is PT. Sapadia Wisata Medan which is engaged in the hotel/lodging sector in the city of Medan. Where the company has 5 lodging properties and of course has a lot of inventory mutation transactions and transactions in and out of stock goods. The obstacle faced by the company is the absence of an information system for inventory. So that many problems occur because of the absence of an information system. The design uses UML (Unified Modeling Language) diagrams, namely use-case diagrams, class diagrams and activity diagrams).